Evolution of dust temperature of galaxies through cosmic time as seen by Herschel - Hwang, H; Elbaz, D; Magdis, G; Daddi, E; Symeonidis, M; Altieri, B; Amblard, A; Andreani, P; Arumugam, V; Auld, R; Aussel, H; Babbedge, T; et al. (2010)
We study the dust properties of galaxies in the redshift range 0.1 ≲z≲ 2.8 observed by the Herschel Space Observatory in the field of the Great Observatories Origins Deep Survey-North as part of the PACS Extragalactic Probe (PEP) and Herschel Multi-tiered Extragalactic Survey (HerMES) key programmes. Infrared (IR) luminosity (LIR) and dust temperature (Tdust) of galaxies are derived from the spectral energy distribution fit of the far-IR (FIR) flux densities obtained with the PACS and SPIRE instruments onboard Herschel. As a reference sample, we also obtain IR luminosities and dust temperatures of local galaxies at z < 0.1 using AKARI and IRAS data in the field of the Sloan Digital Sky Survey. We compare the LIR-Tdust relation between the two samples and find that the median Tdust of Herschel-selected galaxies at z< 0.5 with LIR≲ 5 × 1010L· appears to be 2-5 K colder than that of AKARI-selected local galaxies with similar luminosities, and the dispersion in Tdust for high-z galaxies increases with LIR due to the existence of cold galaxies that are not seen among local galaxies. We show that this large dispersion of the LIR-Tdust relation can bridge the gap between local star-forming galaxies and high-z submillimetre galaxies (SMGs). We also find that three SMGs with very low Tdust (≲20 K) covered in this study have close neighbouring sources with similar 24-μm brightness, which could lead to an overestimation of FIR/(sub)millimetre fluxes of the SMGs. © 2010 The Authors. Journal compilation © 2010 RAS.